2021
DOI: 10.1259/bjr.20201288
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging review of uncommon peritoneal-based neoplasms: beyond carcinomatosis

Abstract: Pathologic involvement of the peritoneum can result from a wide variety of conditions, including both neoplastic and non-neoplastic entities. Neoplastic involvement of the peritoneal ligaments, mesenteries, and spaces from malignant spread of epithelial cancers, termed peritoneal carcinomatosis, is frequently encountered at CT evaluation. However, a host of other more unusual benign and malignant neoplasms can manifest with peritoneal disease, including both primary and secondary peritoneal processes, many of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is generally reported that PMP peritoneal implants are cystic lesions (17,18). However, one case report showed that PMP could also manifest as a cystic-solid mass (19).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally reported that PMP peritoneal implants are cystic lesions (17,18). However, one case report showed that PMP could also manifest as a cystic-solid mass (19).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with suspected PeM, the NCCN Guidelines for Mesothelioma: Peritoneal recommend an initial evaluation including (1) CT with contrast of the chest, abdomen, and pelvis; (2) biopsies of the nodule/mass using a midline laparoscopy; and (3) serum markers. 21,42,43 Pathology Tissue biopsy of the abdominal mass/nodule(s) with histopathology is essential for an accurate diagnosis of PeM, because symptoms, imaging findings, and serum markers are not specific. Patients may have benign and preinvasive mesothelial tumors such as peritoneal inclusion cyst, welldifferentiated papillary mesothelial tumor, or mesothelioma in situ.…”
Section: Initial Evaluationmentioning
confidence: 99%
“…10 ). Psammomatous calcifications within nodules may be seen in up to 30% of cases [ 2 , 31 , 33 ]. Elevation of serum levels of CA-125 is also present in the majority of cases [ 2 , 31 ].…”
Section: Primary Tumors Of the Peritoneummentioning
confidence: 99%